ANALISIS HUKUM TINDAK PIDANA PEGAWAI NEGERI SIPIL SEBAGAI PELAKU PIDANA KORUPSI PENGADAAN BARANG (STUDI PUTUSAN NO.114/PID.SUS-TPK/2018/PN.MDN) - MONALISA SIAHAAN (LP2MTBM MAKARIOZ, 2021)
Criminal acts are a term that is officially used in indonesian laws and regulations. In the writings of Indonesian criminal lawexperts, sometimes the term